Pengembangan Sistem E-Catering Berbasis Web Terintegrasi Whatsapp Gateway Pada Usaha Katering Kembang Desa Ngentrong - Amartya Bambang Kusuma; Joko Iskandar; Yayak Kartika Sari (Universitas Serang Raya, 2025)
This study aims to design a web-based e-catering system integrated with WhatsApp Gateway for the Kembang Desa Ngentrong catering company. This system is intended to simplify and streamline the process of ordering, paying, and reporting catering orders online so as to improve operational efficiency and customer satisfaction. The development approach used is Agile Development, which facilitates the system development process iteratively and collaboratively by actively involving stakeholders. The implementation of WhatsApp Gateway as an integrated communication channel facilitates the ordering process by customers directly through the popular WhatsApp application. This system is developed based on web technology with product menu selection features, order confirmation, automatic alerts, and transaction reports that can be accessed by business owners. The results of system testing show that the use of the Agile Development approach can accelerate the development process and produce products that are in accordance with user needs with a validation scale of